In Vitro Effects of VA441, a New Selective Cyclooxygenase-2 Inhibitor, on Human Osteoarthritic Chondrocytes exposed to IL-1β - Antonella Fioravanti; Laura Tinti; Nicola Antonio Pascarelli; Angela Di Capua; Antonello Lamboglia; Andrea Cappelli; Mariangela Biava; Antonio Giordani; Silvia Niccolini; Mauro Galeazzi; Maurizio Anzini (Elsevier, 2012)
The aim of this in vitro study was to examine the possible effect of [2-methyl-5-(4-methylsulphonyl)phenyl-1-phenyl-3-(2-n-propyloxyethyl)]-1H-pyrrole (VA441), a new selective cyclooxygenase (COX)-2 inhibitor, on human osteoarthritic (OA) chondrocyte cultivated in the presence or absence of interleukin-1β (IL-1β). In particular, we assessed the effects of 1 and 10 μM of VA441, celecoxib, and indomethacin on cell viability, COX-2 and inducible nitric oxide synthase (iNOS) gene expression, prostaglandin E2 (PGE2) production, and nitric oxide (NO) and metalloproteinase-3 (MMP-3) release. Furthermore, we carried out morphological assessment by transmission electron microscopy (TEM). The presence of IL-1β led to a significant increase in PGE2, MMP-3, and NO production, as well as a significant increase in gene expression of COX-2 and iNOS. All the drugs tested had a statistically significant inhibitory effect on PGE2 production and gene expression of COX-2 stimulated by IL-1β. VA441 and celecoxib significantly suppressed IL-1β-stimulated MMP-3 and NO and iNOS gene expression in a dose-dependent manner, while indomethacin did not show any significant effect on MMP-3 and NO production or on iNOS gene expression. TEM demonstrated that IL-1β severely alters the structure of chondrocytes; after coincubation with VA441 or celecoxib, the cells recovered their ultrastructure. Our data suggest that VA441 and celecoxib may have a beneficial effect on chondrocyte metabolism. Keywords:: VA441, celecoxib, indomethacin, cyclooxygenase-2 inhibitor, chondrocyte